2010
DOI: 10.1002/ijc.24914
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐targeted intracellular delivery of anticancer drugs through the mannose‐6‐phosphate/insulin‐like growth factor II receptor

Abstract: Tumor-targeting of anticancer drugs is an interesting approach for the treatment of cancer since chemotherapies possess several adverse effects. In the present study, we propose a novel strategy to deliver anticancer drugs to the tumor cells through the mannose-6-phosphate/insulin-like growth factor receptor (M6P/IGF-IIR) which are abundantly expressed in several human tumors. We developed a drug carrier against M6P/IGF-II receptor by modifying human serum albumin (HSA) with M6P moieties. M6P-HSA specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 35 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…4446 Indeed, several therapeutic strategies (both experimental and already in the clinics) are based on M6PR targeting. 41,4451 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4446 Indeed, several therapeutic strategies (both experimental and already in the clinics) are based on M6PR targeting. 41,4451 …”
Section: Resultsmentioning
confidence: 99%
“…43,44,46,47 and is often used for intracellular transport of therapeutics. 41,4851 Also, there is relatively high expression of TfR associated with various malignancies, it allows transport across the blood-brain barrier, and has been well documented in the context of targeted drug delivery. 42,69,70 An example of an application of targeting these receptors is that of enzyme replacement therapies for treatment of genetic lysosomal storage disorders, where recombinant lysosomal enzymes are injected in circulation and need to be endocytosed by cells in the affected tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In case of targeting moiety-modified nanoparticles, the distribution levels to other organs are still substantial. A recent study reported that 50% of albumin modified with mannose-6-phosphate as a targeting moiety was found to distribute to the liver, with less than 5% of the dose reaching the tumor tissue [42]. Moreover, some targeting moieties on nanoparticles can even enhance the distribution to the liver.…”
Section: Discussionmentioning
confidence: 98%
“…In follow-up studies, M6P-HSA was conjugated to several drugs with anti-proliferative or antifibrotic potential, including doxorubicin, mycophenolic acid, 15-deoxy-Δ12,14-prostaglandin J2 (15dPGJ2) and so forth. (see also Table 1 ) [ 127 , 128 , 129 ]. All drug conjugates demonstrated superior antifibrotic activity in vivo compared to systemic application of their unconjugated counterparts.…”
Section: Cell Specific Targeting Of Caf With Nanoparticlesmentioning
confidence: 99%